Unified methodology for characterisation of global fatigue damage evolution in adhesively bonded joints - Pankaj R. Jaiswal; Rahul Iyer Kumar; Wim De Waele (Fracture and Structural Integrity)
This paper reports on the development of a methodology for evaluating the fatigue damage evolution in single and double lap adhesively bonded joints subjected to constant and variable fatigue loading. First, a methodology is developed to monitor the evolution of permanent deformation, stiffness degradation and hysteresis losses of single lap joints subjected to constant amplitude fatigue load. During the test, the global deformation of the adhesive joint is monitored using digital image correlation (DIC). A MATLAB code is developed to analyse and visualize the evolution in stiffness degradation and energy dissipation during the course of a complete fatigue test. Hereto ellipses are fitted to the hysteresis loops in the recorded load-deformation data. The slope of the main axis of the ellipse and its enclosed area are extracted to determine stiffness and dissipated energy, respectively. Next, the methodology is optimized for implementation during fatigue testing of double lap joints with different bond line thicknesses. The results of the experimental study reveal a distinct relation between stiffness degradation and increase in hysteresis losses with increasing number of fatigue cycles or thus increasing fatigue damage.